Japan’s interests in the Arctic region and prospects for cooperation with Russia - Korneev K.A.; Kistanov V.O. (Восточная Азия: факты и аналитика)
Japan has a number of specific interests in the Arctic region, which in their current form emerged near the end of the 2000s. Firstly, the authors discuss using the transport capabilities of the Northern Sea Route, which can potentially have a significant positive effect on the development of the Japanese economy not only by diversifying hydrocarbon supply routes, but also as a shorter logistics leg for the export of goods, mainly to European countries. Secondly, the exploitation of the natural resources of the Arctic is of great importance for Japan – whereas it is a resource-deficient country, participation in such projects is always relevant. It is obvious that Japanese interests in the Arctic region will be far from practical implementation without interaction with Russia, despite the serious deterioration of bilateral relations due to Japan’s accession to anti-Russian sanctions imposed by Western countries in connection with the Special military operation in Ukraine. Cooperation with Russia in the Arctic region is still ongoing, mostly within the framework of the joint implementation of the Arctic LNG-2 energy project. However, there are other areas, which will also be discussed in this article.